1996
DOI: 10.1152/jappl.1996.81.5.2142
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic blood pressure response is greater during the luteal phase of the menstrual cycle

Abstract: We investigated the cardiovascular responses to acute hypercapnia during the menstrual cycle. Eleven female subjects with regular menstrual cycles performed hypercapnic rebreathing tests during the follicular and luteal phases of their menstrual cycles. Ventilatory and cardiovascular variables were recorded breath by breath. Serum progesterone and estradiol were measured on each occasion. Serum progesterone was higher during the luteal [50.4 +/- 9.6 (SE) nmol/l] than during the follicular phase (2.1 +/- 0.7 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
(30 reference statements)
4
15
2
Order By: Relevance
“…Again, significantly higher serum progesterone level observed in luteal phase than follicular phase is in consistent to that of some authors 5,7,13 .…”
Section: Resultssupporting
confidence: 92%
“…Again, significantly higher serum progesterone level observed in luteal phase than follicular phase is in consistent to that of some authors 5,7,13 .…”
Section: Resultssupporting
confidence: 92%
“…Values of estrogen and progesterone were published in our previous article 8 .These results are consistent with the results observed by Edwards et al 9 and Tanaka et al 10 . Again serum progesterone level during luteal phase was significantly higher than follicular phase.…”
Section: Discussionsupporting
confidence: 92%
“…Again serum progesterone level during luteal phase was significantly higher than follicular phase. Similar results had been observed by Sato et al 1 , Edwards et al 9 and Tanaka et al 10 .…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, some recent studies have reported benefits of administering CPAP to females with PET [35,36]. In theory, the rise in carbon dioxide tension that would occur during inspiratory flow limitation could lead to sympatho-excitation and marked hypertension due to progesterone-mediated upregulation of catecholamine receptors [37].…”
Section: Sdb and Ed In Pet D Yinon Et Almentioning
confidence: 99%